Whole body vibration: Acute and residual effect on the explosive strength - de Hoyo Lora, M.; Granados, S. R.; Corrales, B. S.; Paez, L. C. (Journal of Human Sport & Exercise, 2010)
The whole body vibrations (WBV) it is nowadays one of the most widely used methods for improving the explosive strength. This seems to produce similar effects than those found after applying a eccentric-concentric cycle. In this study, 12 subjects participating in recreational physical activity were allocated to 5 sets of 60 s of WBV exposure, using a frequency of 30 Hz, and 2.5 mm of amplitude, maintaining an static position (110 ° bending knees) on a vibratory platform (Galileo Fitness®; Novotech, Germany). The results showed an increase (not significant) in SJ (+1.76 ± 4.05 cm) and CMJ (+1.10 ± 3.20 cm) in the post-test conducted just after the vibration. The values of the post-test performed 30 min after SJ remained above the pre-test ones but just below the immediate post-test ones (+0.42 ± 4.43 cm). By contrast, the values in CMJ dropped below the pre-test ones (-0.12 ± 2.45 cm). Based on these data it seems that when the frequency is not high it is necessary to use greater amplitude in order to achieve the desired effects. The effect achieved after the vibration is transient, not remaining after 30 min.